2010
DOI: 10.1159/000320570
|View full text |Cite
|
Sign up to set email alerts
|

Reference Profile Correlation Reveals Estrogen-like Trancriptional Activity of Curcumin

Abstract: Background: Several secondary metabolites from herbal nutrient products act as weak estrogens (phytoestrogens), competing with endogenous estrogen for binding to the estrogen receptors and inhibiting steroid converting enzymes. However, it is still unclear whether these compounds elicit estrogen dependent transcription of genes at physiological concentrations. Methods: We compare the effects of physiological concentrations (100 nM) of the two phytoestrogens Enterolactone and Quercetin and the suspected phytoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…Indeed, curcumin displaced estradiol binding to its receptors [19; unpublished observations]. In breast cancer cells, curcumin elicited gene expression profiles typical of estrogen/phytoestrogen actions [20,21]. Estradiol (akin to a hexane extract of Curcuma comosa) reduced seminal vesicle weights in mice [22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, curcumin displaced estradiol binding to its receptors [19; unpublished observations]. In breast cancer cells, curcumin elicited gene expression profiles typical of estrogen/phytoestrogen actions [20,21]. Estradiol (akin to a hexane extract of Curcuma comosa) reduced seminal vesicle weights in mice [22].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics appears to be the link between environment-associated diseases, nutrition and health. Nutrients can modify the epigenetic program and influence gene expression therefore controlling the intake of functional food components through diet can be powerful in preventing agerelated and other diseases including cancer [12][13][14]. It is emerging a novel view of food and metabolites, in contraposition to the classical paradigm based on the chemical conversion of food in energy and body mass.…”
Section: Non-coding Rnas (Ncrnas)mentioning
confidence: 99%
“…In most studies high concentrations of the compounds are used in order to obtain measurable effects. We have recently shown that the phytochemicals curcumin, enterolactone and quercetin have estrogenic effects on gene transcription even at low, physiological concentrations that become evident by the correlation analysis of estradiol and phytoestrogen induced gene expression profiles [37]. …”
Section: Phytoestrogensmentioning
confidence: 99%
“…After the advent of genomic technologies, nearly a decade ago, the capability of a molecule to produce estrogenic effects in vitro is usually evaluated by gene expression profiling [37, 96-99]. This analysis, based on the comparison between the gene expression changes induced by E2 and by the substance to be tested, has shown that E2 regulates the expression of hundreds of genes [99, 100].…”
Section: Effects Of Phyto- and Xenoestrogens On Human Breast Tissuementioning
confidence: 99%